Totalitarianism in George Orwell's Animal Farm - Mujtaba Muhammedali Yahya Al-Hilo; Hayder Ali Gebreen (RIRAI Publisher, 2021)
The Animal Farm attempts at representing a realistic analysis of the revolution and changing of systems and regimes. However, change may not be necessarily a positive one as long as there is not a just and fair system upon which the sons of the revolutions depend. As history has proved, the majority of revolutions fail to achieve the utopian goals they had been seeking. Then, it fails to achieve the goals that are sought from it. Eventually, the reality becomes worse than that which it aimed to change. Since the theme of this novel is applicable for all people in any place at any time, and the big role that political discourse played in its event, we have chosen it to be our subject to analyze and discuss in our graduation project. After this short abstract, we will present an introduction in which we show the author’s contribution in the world of literature, his famous works and their significance. After that, we move on to deal with the language and discourse, rhetoric speech and discourse of Orwel and his ideology. The we tend to cover the author’s life, political discourse, and finally the political discourse of the author in The Animal Farm. We end our paper with a conclusion which includes our points of view to the importance of the political discourse in the novel and the moral lessons the mankind can draw out from such great piece of literature.